Dog Food Consumption in the Caribbean: A Baseline Study - Fielding, William J.; Newman, Mark D. (International Journal of Bahamian Studies, 2013)
Dogs in the Caribbean have been traditionally viewed as low maintenance pets which are fed leftovers from the household. Changes in the lifestyle of Caribbean families have resulted in changes in their eating patterns. These changes can be expected to have consequences for the feeding of dogs, which may require households to switch to commercial dog food. This paper reports the finding of a survey of groups involved with pets and animal welfare in the Caribbean conducted on behalf of the Pet Food Institute, a non-profit industry association. The study examined perspectives on how dogs are fed in the Caribbean and activities conducted to educate pet owners and the public. Use of household scraps and commercial dog food was associated with household income, except in the case of some high income dependent territories. The findings indicate that while many animal welfare groups in the Caribbean provide educational programs, not all of these provide recommendations on feeding pets and so they neglect to provide information on an important aspect of animal welfare.